A case report of rare intraperitoneal cholesteatoma diagnosed and treated through multidisciplinary collaboration. Issue 10 (7th July 2020) - Jiang, Jie; Chu, Guang; Chen, Gang; Liao, Hongyun; Yu, Lu; Yu, Hongjun; Liu, Jie; Hu, Zongqiang
Abstract: 55‐year‐old female patient with abdominal distension and poor appetite for 3 months was diagnosed as intraperitoneal cholesteatoma by imaging findings and histological tests. Patient has received surgical resection and recovered well after operation. Abstract : 55‐year‐old female patient with abdominal distension and poor appetite for 3 months was diagnosed as intraperitoneal cholesteatoma by imaging findings and histological tests. Patient has received surgical resection and recovered well after operation.